THE IMPACTS OF ECONOMIC AND SOCIAL LAND CONCESSIONS IN CAMBODIA (2000-2017): A REVIEW OF MECHANISMS, OUTCOMES, AND FAILURES - Toeung, Socheat; So, Maly; Ros, Ravuth (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Following the implementation of the economic and social land concession policy, Cambodia has witnessed significant societal progress. However, challenges persist, as not all citizens have access to employment that aligns with market demands. The introduction of economic land concessions has created new opportunities for individuals residing both near and far from these areas, enabling them to secure employment and enhance their quality of life. For example, the development of rubber plantations has increased the demand for skilled labor, benefiting local residents by providing jobs and improving living standards. These employment opportunities help individuals afford essential needs such as food, shelter, and clothing, particularly when working far from home. The government's primary objective is to improve the quality of life for its citizens and alleviate poverty, a critical step toward national development and global competitiveness. Furthermore, the Royal Government of Cambodia has instituted innovative policies to foster sustainable economic growth. These policies utilize media and associated institutions to attract investment, including from foreign investors, by facilitating diplomatic initiatives abroad. Economic land concessions are specifically intended to serve economic interests, necessitating substantial financial contributions from both the government and investors. While these concessions can stimulate economic growth, their effects are varied. Reports indicate both positive outcomes, such as enhanced livelihoods, and negative consequences, including land disputes, workplace challenges, and adverse impacts on indigenous communities